NOMOR POKOK WAJIB PAJAK (NPWP) DAN PENGUSAHA KENA PAJAK (PKP) - Abuyamin, Oyok (Sekolah Tinggi Hukum Bandung, 2010)
Every taxpayer who has fulfilled subjective and objective qualification in accordance with provision and Taxation Act has an obligation to register to Directorate General of Tax where its working area covers the residence or position of the taxpayers and to them are given Registered Number of Taxpayer Subject (NPWP). Then, every taxpayer as a taxable entrepreneur based on Value Added Taxation Act year 1984 and its amendmentÂ has anobligation to send their business reports to the office of Directorate General of Tax where its working area covers the residence or position of the taxpayers and their places of business to become taxable entrepreneurs.Keywords: Self Assessment Â Registered Number of Taxpayers Subject: Taxable